Євген Богуславський: проблеми співпраці з політичними режимами - Давидюк, Руслана Петрівна; Davydiuk, Ruslana (Східноєвропейський національний університет імені Лесі Українки, 2017)
У науковій статті на основі архівних документів проаналізовано життя педагога, очільника Вінницької міської філії Подільської губернської української ради Євгена Богуславського, який після поразки революції, емігрував до Польщі. У міжвоєнний період учителював, був послом польського сейму, займався політичною, редакторською, церковно-релігійною діяльністю у Волинському воєводстві. З’ясовано невідомі донині обставини життя Є. Богуславського в умовах нацистського та більшовицького режимів. The article analyses life of educator, the chief of Vinnytsya City Branch of Podolian Provincial Ukrainian Council Yevhen Boguslavsky, who was the down of and was the director of Vinnytsya Ukrainian gymnasium on the basis of the archival documents. As a representator of a zemstwo`s council, in May 1920 he organized the meeting of Josef Pilsudski and Simon Petliura at the railway station. After the fail of revolution he emigrated to Poland and settled in Volhyn Voivodeship. In the interwar period he worked as a teacher, was a member of Polish Sejm, he was engaged in political, editorial, cooperative and religious activities in Volhynian Voivodeship. He`s known as an initiator of formation of «The Association named after metropolite Petro Mogyla» and «Volhynian public committee of aid for starving in Soviet Ukraine». On the basis o archival materials the article enquires Yevhen Boguslavsky`s life circumstances which were unknown to this day, as a prisoner of the «Montelupi» under the conditions of Nazi occupation. Cooperation between Yevhen Boguslavsky and Bolshevik secret services in Soviet period and is arrest by the MSS is observed.
Yevhen Boguslavsky: the Problems of Cooperation with Political Regimes
Keywords: українська революція; політична еміграція; посол; нацистський режим; більшовицька влада; МДБ; Ukrainian revolution; political emigration; ambassador; Nazi regime; Bolshevik authorities; MSS